2012
DOI: 10.5812/nephropathol.7534
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury: A pediatric experience over 10 years at a tertiary care center

Abstract: Implication for health policy/practice/research/medical education:The etiology of acute kidney injury (AKI) varies in different countries. In a retrospective analysis data of 180 children less than 18 years treated for AKI was studied. We concluded that the mortality is still high in AKI. The poor outcome (defined as low GFR) are higher among patients with low levels of first GFR and higher RIFLE score.Please cite this paper as: Gheissari A, Mehrasa P, Merrikhi A, Madihi Y. Acute kidney injury: A pediatric exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
2
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 20 publications
2
15
2
3
Order By: Relevance
“…It was found that life expectancy of the patients who began dialysis above 75 years old was significantly shorter than the patients who started dialysis between 50 and 60 years of age, especially if they had low weight, lost weight loss and/or required hospitalization [43]. Negative association of age with dialysis efficiency seriously influences the life expectancy of older patients [1][2][3][4][5][6]. We showed the negative association of age and predialysis serum creatinine.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…It was found that life expectancy of the patients who began dialysis above 75 years old was significantly shorter than the patients who started dialysis between 50 and 60 years of age, especially if they had low weight, lost weight loss and/or required hospitalization [43]. Negative association of age with dialysis efficiency seriously influences the life expectancy of older patients [1][2][3][4][5][6]. We showed the negative association of age and predialysis serum creatinine.…”
Section: Discussionmentioning
confidence: 79%
“…Trends have changed and now over 35% of chronic dialysis patients are 65 or older, when starting dialysis therapy [1][2][3][4][5][6]. Currently, there are around one million chronic dialysis patients worldwide [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Almanya 2011 salgınından sonra Türkiye'de yaşanan kısmi salgın ve farkındalığın artması nedeni ile diyare ilişkili hemolitik üremik sendromu (D+HÜS) daha sık görülmeye başlanmıştır. 6,7 Ancak HÜS tanısı koyarken tanı kriterleri dikkatle değerlendirilmediği takdirde akut renal zedelenme nedeni atlanabilmekte ve hastanın tedavisi gecikebilmektedir.…”
unclassified
“…Hence, it is well established that there is a gender difference in the cisplatin renal toxicity in rat model. Indeed, it is well recognized that some conditions that lead to chronic kidney diseases are sex related too; [5][6][7][8][9][11][12][13] however, few studies published regarding gender difference in cisplatin renal toxicity . However, there still needs to be more investigations, mechanisms take part in cisplatin renal toxicity especially on gender difference.…”
mentioning
confidence: 99%